Modelling with BRG.LifeMODTM in sport science - Hofmann, M.; Dänhardt, M.; Betzler, N.; Witte, K.; Edelmann-Nusser, J. (International Journal of Computer Science in Sport, 2006)
Besides the actual state of the condition, the performance of an athlete is highly influenced by the way of executing the movement. So this factor is said to be more and more important. In order to find out and use these potentials, sport science profits from the power of computers for example with modelling and simulating special movements. This article describes the basic functions of a modelling software (BRG.LifeMOD™) using the field of inverse dynamics. Additionally, the results of a first application will be presented, showing a comparison between the forces while walking over a forceplate and the calculated forces with BRG.LifeMOD™ based on inverse dynamic. The data gives evidence that the use of the modelling software can be quite useful in future.